2018
DOI: 10.1093/conphys/coy021
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes of faecal cortisol metabolite levels in Gracilinanus agilis (Didelphimorphia: Didelphidae) and its association to life histories variables and parasite loads

Abstract: FCMs are a reliable indicator of adrenal activity in G. agilis. There is an association among stress response, reproductive status and weather. Environmental stress rises in the probability of Eimeria spp infection in G. agilis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Our study greatly adds to the literature on glucocorticoid concentrations in wild small mammals, specifically animals in the genera Oligoryzomys, Akodon, Gracilinanus, and Marmosa. In a review of the published literature, we found only one publication on Gracilinanus that provided information regarding glucocorticoid concentrations in these small mammal genera 54 . Our study provides fur corticosterone and cortisol levels for freeranging small mammals in a fragmented landscape, and emphasizes the need for a better understanding of these glucocorticoid levels for animals living in less-disturbed forest environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study greatly adds to the literature on glucocorticoid concentrations in wild small mammals, specifically animals in the genera Oligoryzomys, Akodon, Gracilinanus, and Marmosa. In a review of the published literature, we found only one publication on Gracilinanus that provided information regarding glucocorticoid concentrations in these small mammal genera 54 . Our study provides fur corticosterone and cortisol levels for freeranging small mammals in a fragmented landscape, and emphasizes the need for a better understanding of these glucocorticoid levels for animals living in less-disturbed forest environments.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings that found a relationship between the extent of habitat disturbance and glucocorticoid levels 36,39,40 , we predicted that glucocorticoid levels would negatively correlate with the size of the forest fragment in which the animals were captured, so that small mammals in smaller forest fragments would have higher glucocorticoid levels than small mammals in larger forest fragments. However, because patterns have varied in studies of animals in human-impacted landscapes, and there can be confounding factors that affect glucocorticoid levels 53 , including the impact of capture stress 54 , we included ecomorphological factors and sampling methods in the analyses. Given that factors associated with glucocorticoid levels are not fully apparent broadly across taxa, as well as within small mammal taxa, our research findings can contribute information about the physiological ecology of wild small mammals living in fragmented landscapes.…”
mentioning
confidence: 99%
“…high prevalence of B. schroederi ) nor increased the cortisol levels. This seems to be inconsistent with the nutritional restriction hypothesis, which suggests that food and water shortages that act as stressors can elevate cortisol levels and parasitic infections in wild animals ( Chapman et al ., 2006 ; Behie and Pavelka, 2013 ; Hernandez et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, behavioural attributes (such as decreased activity) will also be implemented to withstand the temperatures ( Wingfield, 2013 ). In seasonal environments, there is a strong association between the dry season and increased GC concentration owing to food and water shortages ( Davies et al, 2013 ; Hernandez et al ., 2018 ). For example, an increase in GC levels during seasonal dry periods ensures a constant source of energy through the metabolism of stored fat as shown in Magellanic penguins ( Spheniscus magellanicus ; Walker et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%